Locating Optimum Receiver Position in Seismic Acquisition: Example from Carbonate Region - ., Abdul Halim Abdul Latiff, Zulfadhli Mohd Zaki, Siti Nur Fathiyah (2017)
The existence of carbonate pinnacle disrupts the propagation of seismic wave from source to receivers, thus creating un-illuminated reflectors image. In previous years, several methods have been studied and applied in order to improve the subsurface data by restoring true reflectivity, with certain degrees of success. We can improve the seismic images in hand either by the implementation of complex migration algorithm or by conducting a fresh seismic data acquisition within the affected region. Following the seismic value chain, we can easily analyse the quality of the seismic images before any new acquisition took place through the forward modelling procedure using synthetic data for illumination analysis. In current illumination procedure, the required inputs are velocity model, acquisition set-up and the wave propagation. Although velocity information and wave propagation parameters are generally consistent within a basin, the seismic acquisition set-up needs to be revolutionized in order to bring a higher subsurface illumination. In this work, we proposed an optimum receiver position by using the particle swarm optimization approach, for better seismic images in carbonate-affected region